MENINGKATKAN MEMBACA HURUF HIJAIYAH MELALUI PERMAINAN KARTU HURUF PADA ANAK USIA DINI KELOMPOK B DI TK AL-AMIN - Ramadani, Ravida (Jurnal Al-Fatih, 2024)
This study aims to improve the ability to read Hijaiyah letters among early childhood students in Group B at TK Al-Amin Labuhanbatu Utara through the use of the letter card game method. The type of research used is Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 30 children divided into two classes, B1 and B2. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results showed a significant improvement in the children’s ability to read Hijaiyah letters from the pre-cycle to the second cycle. In the pre-cycle, most children were in the not yet developed and starting to develop categories, but after the implementation of the letter card game, their reading skills increased to the developing as expected and very well developed categories in the second cycle. In conclusion, the application of the letter card game method is effective and enjoyable in improving the ability to read Hijaiyah letters among early childhood students at TK Al-Amin Labuhanbatu Utara.